2016
DOI: 10.1007/s12024-016-9786-9
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine toxicity in forensic practice: possible effects and under-appreciated sources

Abstract: Caffeine is considered a very safe stimulant and is widely consumed in a variety of forms, from pure caffeine to beverages and foods. Typically, death is only seen when gram quantities of caffeine are consumed, usually in suicide attempts. Even in this scenario, death is rare. However, there are special populations that need to be considered in forensic presentations, who may be at greater risk. These include poor metabolizers, people with liver disease, and people with cardiac conditions, who can die as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…A major issue with in vitro studies using caffeine is whether the concentrations utilised are biologically relevant [24, 45]. In the current study a significant effect was observed at levels down to 100 μM which is consistent with the IC50 (75 μM) reported for p110δ inhibition [23] and considerably lower than the plasma levels considered to be toxic (400 μM) [46, 47]. A recent study has reported human hemopoietic cells actively take up caffeine and that, in acute myeloid leukemia cells, caffeine inhibited signalling downstream from PI3K at concentrations as low as 100 μM [48].…”
Section: Discussionsupporting
confidence: 86%
“…A major issue with in vitro studies using caffeine is whether the concentrations utilised are biologically relevant [24, 45]. In the current study a significant effect was observed at levels down to 100 μM which is consistent with the IC50 (75 μM) reported for p110δ inhibition [23] and considerably lower than the plasma levels considered to be toxic (400 μM) [46, 47]. A recent study has reported human hemopoietic cells actively take up caffeine and that, in acute myeloid leukemia cells, caffeine inhibited signalling downstream from PI3K at concentrations as low as 100 μM [48].…”
Section: Discussionsupporting
confidence: 86%
“…He had no pre-existing heart condition (Reuters News Agency, April, 2017). These two reports, coupled with statistics published in recent reviews [15] [16] [17], provide convincing evidence that caffeine can be lethal.…”
Section: [16] [17]))mentioning
confidence: 80%
“…With additional treatment, including several weeks in a psychiatric unit, this patient made a full recovery. Her circulating plasma caffeine concentrations six and eighteen hours after ingestion were 240 and 150 µg/ml [14] (note: 80 -100 µg/ml caffeine can be fatal (see refs [15]…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, there has been limited detailed research regarding caffeine fatalities and there have been sporadic reports about it, although complete reviews have been published on the topic of caffeine [ 5 , 6 , 7 ]. The aim of this systematic review is to summarize data regarding caffeine lethal intoxications and try to identify possible categories at risk for it; data obtained from our study could support both clinicians and pathologists in identifying possible unrecognized cases and render possible a better and further comprehension of an ever-growing phenomenon.…”
Section: Introductionmentioning
confidence: 99%